Facebook as a Peer-Assessment Platform: A Case Study in Art Teacher Education Context - Yasemin Ersöz; Süleyman Nihat Şad (International Journal of Assessment Tools in Education)
This research intended to answer the question “IsPeer-Assessment on Facebook useful in visual art education?” in an intrinsiccase study. Participants were a group of prospective visual-art teachers, whoregularly share and comment on the photographs of their paintings in a specialgroup they created on Facebook. Ten volunteering prospective visual-artteachers were involved in the study during 2013-2014 academic year. Focus groupinterviews were conducted with the participants to collect data in addition toonline digital documents, including photographs of students’ paintings andcomments on them. In general, participants stated that Facebook-based peerassessment is beneficial, since it helps them notice their deficiencies, lookat their works from a different perspective and improve their artistic skills.Thanks to the productive feedback, their motivation and self-confidence are boosted.It was also found that peer-assessment on Facebook has the advantage ofubiquity, allowing more peer involvement, easy and objective criticism, andsustainable learning opportunities in the long-run. The participants alsoemphasized some disadvantages of the practice of peer assessment on Facebooksuch as subjective feedback and poor quality of digitalized visuals.